Vivir la comunión en la diferencia en tiempos de posmodernidad. Una reflexión teológica a la luz de Joseph Ratzinger (2021)
Man is a relational being, built and maintains the relationships that he establishes with other. This condition comes from having been created in the image and likeness of God, who is a community of people, a God who is in relationship with love and who imprints this seal on his creature. However, he can ignore this condition and wish to live in the illusion of autarky, of the complete autonomy that leads him to the denial of his being, to loneliness, fear and death, which are at the root of all types of disagreement in which humanity lives today and from which only the personal closeness of someone who loves him can save him. This is precisely what God, in Christ, does for humanity. He shows the way to recover the relationship with the Other, that starting from the meeting leads to the intimate experience of communion in love. This can be today, a hopeful way in front of the multiple signs of the postmodern culture, especially, to the fragility of the personal ties, which plunges many people into loneliness and nonsense; at the same time a challenge for the disciples of Christ.